PENGARUH BERCERITA DENGAN MEDIA BONEKA JARI BERBAHAN ORIGAMI TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN DI TK ANGREK KECAMATAN TAPUNG KABUPATEN KAMPAR - Reni Amiliya Amiliya; Wilson '; Yeni Solfiah Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is based on observations on the ability to listen of children age 4-5 years who are still low. So, it is necessary to use finger puppet as media made from origami. This research aims to determine the effect of storytelling by using finger puppets media on the ability to listen of children aged 4-5 years in ANGGREK kindergarten, Tapung district of Kampar regency. The sampel used in this research are 28 people. The data collection techniques were use is observation. Data were analyzed using t-test using SPSS 16.0. Research hypothesis is that there is a very significant influence on the ability to listen of children aged 4-5 years in ANGGREK kindergarten, Tapung district of Kampar regency after applying storytelling by using finger puppets media. It can be seen from the analysis of data obtained t=48.000 and p=0.000 because p<0.05. It can be concluded that there are the ability to listen of children aged 4-5 years is very significant after using finger puppets media. So it means that h0 is rejected and ha accept which means there is a very significant between before and after doing experiment by using finger puppets media on the ability to listen of children aged 4-5 years in ANGGREK kindergarten, Tapung district of Kampar regency. Key words: The Ability to Listen, Finger Puppets Media Made from Origami